YOUTH EMPLOYMENT AND DIRECTIONS OF ITS REGULATION - Зарифов Бобур (American Journals Publishing, 2025)
In this article, the work carried out in the Republic of Uzbekistan today in terms of youth policy, coverage of young people with higher education, meaningful organization of their free time, ensuring their employment with a profession that fully meets the requirements of today's modern era and world standards is analyzed, and the existing problems and shortcomings are studied.
Keywords: Youth, youth policy, employment, strategy, new Uzbekistan, labor market, green economy, effective employment.